Problems of endodontic treatment according to the survey - A. V. Arutyunov (Кубанский научный медицинский вестник, 2014)
The article presents the results of the survey dentists on problems of endodontic treatment of teeth. The data obtained indicate a low level of knowledge of doctors, the use of inappropriate methods and materials for obturation of root canals. Lack of awareness of physicians, as well as extremely poor knowledge of anatomy of the maxillofacial region, casts doubt on the quality of education and requires a major adjustment curriculum as students and postgraduate level, including training cycles.